2018
DOI: 10.1016/j.jab.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of rice-derived polyphenols on obesity-related oxidative stress and inflammation

Abstract: Global obesity rates are of epidemic proportion. With limited treatments available there is a large demand for therapeutic alternatives. Polyphenols derived from coloured rice varieties may serve as a potential functional food alternative in combating obesity and obesity-related diseases. The antioxidant and anti-inflammatory properties of polyphenols found in coloured rice varieties could have the ability to neutralize oxidative stress and modulate inflammatory responses in obese populations. This review disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…Several studies highlighted the protective effects of polyphenols against oxidative stress. On the one hand, protective effects of the polyphenols rely on their ability to improve cellular antioxidant response by promoting the Nrf2 pathway or by stimulating antioxidant enzymes such as glutathione peroxidase (GPx), catalase or superoxide dismutase (SOD) [ 47 ]. On the other hand, the capacity of polyphenols to act as free-radical scavengers and electron donors give them a protective effect against oxidative stress [ 48 ].…”
Section: Impact Of Infusion and Decoction Process On The Antioxidamentioning
confidence: 99%
“…Several studies highlighted the protective effects of polyphenols against oxidative stress. On the one hand, protective effects of the polyphenols rely on their ability to improve cellular antioxidant response by promoting the Nrf2 pathway or by stimulating antioxidant enzymes such as glutathione peroxidase (GPx), catalase or superoxide dismutase (SOD) [ 47 ]. On the other hand, the capacity of polyphenols to act as free-radical scavengers and electron donors give them a protective effect against oxidative stress [ 48 ].…”
Section: Impact Of Infusion and Decoction Process On The Antioxidamentioning
confidence: 99%
“…Legumes are an excellent source of proteins and, when they are enzymatically digested, they become peptides with multiple sizes that can exert a wide spectrum of biological potentials [ 16 , 17 , 18 ]. Hence, the incorporation of bioactive compounds from legumes into diets could exert beneficial effects by regulating lipid metabolism, resulting in a potential alternative in the prevention or as an adjuvant in the treatment of obesity [ 19 , 20 ]. Furthermore, studies with legume-derived hydrolysates have shown beneficial effects on immunity, inflammation, infection, hypertension, hypercholesterolemia, type 2 diabetes and some types of cancer [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brown rice has potentials in resisting oxidation and antioxidants, diminishing inflammation and reducing blood lipids. This potential of rice-derived polyphenols may potentially regulate risk factors for obesity-related rice and inflammation development [8].…”
Section: Introductionmentioning
confidence: 99%